IMPROVING THE STUDENTS’ READING COMPREHENSION THROUGH WEBTOON APPLICATION AT MTS AZ-ZUHRI TANJUNG MORAWA - Khairani, Alfa (Faculty of Tarbiyah nad Teacher Training, 2022)
The research was intended to find the authentic materials that improving to increase the reading comprehension. The subject of this research was the class VII-A of MTs Az-zuhri. There were 36 students as the samples used in this thesis. The research method used was Class Room Action that done in two cycles. The data were analyzed qualitatively and quantitatively. In qualitative data was got through interview, and observation. For the quantitative data was got through pre-test and pos-test. Based on the qualitative data that found, the using of Webtoon Application can improve studenst‟ responses in reading comprehension. It can be seen in the result of test. In the first cycle, it consist of two meetings. In the first meeting, the students‟ result percentage was 32,5 % (enough) and for second meeting, the students‟ result percentage was 63,8 % (good). In the second cycle the students‟ score was 83,3% (Very good). This score showed that the students‟ average score was improving in every test. The student s‟ average score in pre-test was 13 of 36 students (32,5 %). The percentage of the students‟ who got the score 70 and more in the posttest I was 23 of 36 students (63,1 %). The percentage of the students‟ who got the score 70 and more in the post-test II was 30 of 36 students (83,3 %). The improvement of the competent students percentage from the pre-test to the post-test I was icrease, it is about 50,6 %, from post-test I to post-test II was 20,2 %, pre-test to post-test II was 50,8%. From the data,it showed that the improving of the students‟ reading skill was significant.The results of the research show that using Webtoon Application can improve to the students‟ reading comprehension.